Obesity : Oxidative Stress and Dietary Antioxidants - Marti del Moral, Amelia; Aguilera Garcia, Concepcion Maria (Elsevier Ltd. : Academic Press, 2018)
Obesity: Oxidative Stress and Dietary Antioxidants cover the science of oxidative stress in obesity and associated conditions, including metabolic syndrome, bariatric surgery, and the potentially therapeutic usage of natural antioxidants in the diet or food matrix. The processes within the science of oxidative stress are not described in isolation, but in concert with other processes, such as apoptosis, cell signaling and receptor mediated responses. This approach recognizes that diseases are often multifactorial and oxidative stress is but a single component. The book is designed for nutritionists, dietitians, food scientists, physicians and clinical workers, health care workers and research scientists.